Changing landscape of supply chain in India with multimodal logistics parks: Examining the Role of Multimodal Logistics Parks in India's Changing Supply Chain Landscape (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The changing dynamics of global trade and increasing demand for efficient supply chainoperations have necessitated a paradigm shift in India's logistics infrastructure. Multimodal logistics parkshave emerged as a game-changer in optimizing supply chain efficiency, leveraging multiple modes oftransportation, and addressing critical challenges faced by traditional logistics systems. This researchpaper provides a comprehensive analysis of the changing landscape of supply chain in India, focusing onthe significance and impact of multimodal logistics parks in enhancing overall efficiency andcompetitiveness.